Dinâmicas em sala de aula: uma tentativa de aproximar a língua portuguesa da realidade do educando - Bastolla, Fernanda Falcori (Linguagens & Cidadania, 2017)
The construction of the knowledge in classroom run some ways and, in these ways, it has deep and lasting implications that will reflect in the teach-learning of the students. So, the education comes conquering a new identity that constitutes as an alive and democratic space, evidencing the experiences brought from the students. It was considered as the starting point for the educative dimension of the knowledge.